Long-term consequences of early childhood malnutrition - Alderman, Harold; Hoddinott, John F.; Kinsey, Bill (International Food Policy Research Institute, 2003)
This paper examines the impact of preschool malnutrition on subsequent human capital formation in rural Zimbabwe using a maternal fixed effects-instrumental variables (MFE-IV) estimator with a long-term panel data set. Representations of civil war and drought 'shocks' are used to identify differences in preschool nutritional status across siblings. Improvements in height-for-age in preschoolers are associated with increased height as a young adult and number of grades of schooling completed. Had the median preschool child in this sample had the stature of a median child in a developed country, by adolescence, she would be 4.6 centimeters taller and would have completed an additional 0.7 grades of schooling